When Is the Federal Budget Like a Baby? Metaphor in Political Rhetoric - Read, Stephen J.; Cesa, Ian L.; Jones, David K.; Collins, Nancy L. (Metaphor and symbolic activity, 1990)
The effect of metaphor on responses to political communications was examined. In Study 1, we investigated whether a metaphor could increase memory for a passage and whether the effect might be greater when the passage was heard rather than read. Also examined were the relative effects of having the metaphor present at encoding, at recall, both, or neither. Participants either read or listened to four short passages. For half of the subjects, each passage was preceded by a metaphor. At recall, all subjects were presented with the corresponding metaphor for two of the four passages, as a retrieval cue. As predicted, subjects better recalled the passages when the metaphor was present at encoding. This effect tended to be stronger when the passage was presented orally. Presence of the metaphor at recall had no effect. In addition, presence of the metaphor led to significantly more positive ratings of both the passages and the speaker on a number of characteristics.